2011
DOI: 10.1007/s10709-011-9596-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of 5S rDNA location in acridid grasshoppers and its relationship with H3 histone gene and 45S rDNA location

Abstract: We analyze the chromosomal location of 5S rDNA clusters in 29 species of grasshoppers belonging to the family Acrididae. There was extensive variation among species for the number and location of 5S rDNA sites. Out of 148 sites detected, 75% were proximally located, 21.6% were interstitial, and only 3.4% were distal. The number of 5S rDNA sites per species varied from a single chromosome pair (in six species) to all chromosome pairs (in five species), with a range of intermediate situations. Thirteen chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
50
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 77 publications
9
50
1
Order By: Relevance
“…4C). A. hasemani contains terminal sites on pairs 2, Z, 5,8,12,13,18,20,24,26,27 and at the terminal region on the short arm of the W chromosome (Fig. 4D).…”
Section: Physical Chromosome Mapping Of Repetitive Dnasmentioning
confidence: 99%
See 1 more Smart Citation
“…4C). A. hasemani contains terminal sites on pairs 2, Z, 5,8,12,13,18,20,24,26,27 and at the terminal region on the short arm of the W chromosome (Fig. 4D).…”
Section: Physical Chromosome Mapping Of Repetitive Dnasmentioning
confidence: 99%
“…However, reassociation kinetics based on C o t-1 DNA and the microdissection of chromosomes submitted to C-banding and the subsequent amplification of heterochromatic sequences using degenerate oligonucleotide-primed polymerase chain reaction (PCR) have been used successfully. [9][10][11][12][13][14] The Parodontidae is a Neotropical fish group that is divided into three genera: Parodon, Apareiodon, and Saccodon. 15 Cytogenetic studies reported a conserved diploid number of 54 chromosomes in Parodontidae with distinctive karyotype formulae and numerical/position variation of 18S and 5S rDNA sites.…”
mentioning
confidence: 99%
“…In contrast, studies of 5S rDNA sites in 14 species showed that they are present on more than one chromosome pair in 99.8% of cases; the only exceptions were Chorthippus apicalis and Stauroderus scalaris in which signals are limited to chromosome pairs 6 and 3, respectively (Loreto et al, 2008;Cabral-de-Mello et al, 2011a). These studies show the variation in dispersion of rDNA sequences, which in most species are present on two to five chromosome pairs.…”
Section: Introductionmentioning
confidence: 69%
“…Molecular cytogenetic studies using fluorescence in situ hybridization (FISH) with repetitive DNA probes, such as rDNA and histone genes, have been carried out on many grasshopper species, particularly of the family Acrididae Loreto et al, 2008;Cabrero et al, 2009;Cabral-de-Mello et al, 2011a;Oliveira et al, 2011;Rocha et al, 2011;Jetybayev et al, 2012;Bueno et al, 2013;Palacios-Gimenez et al, 2013). The objective of physical mapping of these and other repetitive DNA sequences is to provide information on chromosome structure and gene distributions in a range of species that would serve as a basis for phylogenetic studies Cabrero et al, 2009;Cabral-de-Mello et al, 2011a,b;Jetybayev et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a large variety of 5S rRNA gene linkages are also found in multicellular eukaryotes. This includes linkages to ribosomal rRNA genes in land plant, nematode, spider and crustacean species, linkages to SL genes in nematode and hydrozoan species and linkages to histone and/or snRNA genes in fish, crustacean, insect and mollusk species (reviewed in Drouin and Moniz de Sá 1995; Pelliccia et al 2001;Eirín-López et al 2004;Cross and Rebordinos 2005;Manchado et al 2006;Derelle et al 2010;Cabral-de-Mello et al 2011;Vierna et al 2011;Wicke et al 2011). The fact that 5S rRNA genes are sometimes found linked to a variety of other genes argues against the linkage of 5S rRNA genes and ribosomal RNA genes being the primitive condition not only in protists but also in other eukaryote species.…”
Section: Fig 2 Phylogenetic Distribution Of 5s Genes Arrangements Inmentioning
confidence: 99%